Analysis of Mathematical Understanding Ability of Grade IV Students in Solving Mathematical Word Problem - Jeujanan, Mariana Jeujanan; Wahyudin, Wahyudin; Mulyasari, Effy; Azzahra, Siti Silmi (proceedings.icesy, 2026)
This study aims to describe the level of mathematical comprehension ability of elementary school students in solving story problems. The research problem departs from the finding that the understanding of basic mathematical concepts in grade IV students still varies, especially in relating concepts to contextual situations. This study uses a quantitative descriptive method in one of the elementary schools in Manokwari Regency. The research subjects were 31 students in grade IV, with data obtained through a description test consisting of ten questions according to five indicators of mathematical comprehension ability. The data collection technique is carried out through the administration of tests, while the data analysis uses descriptive statistics to interpret the tendency of student achievement in each indicator. The results of the study show that students’ mathematical comprehension skills are at a moderate level, with a wide variation in concept mastery between students. Indicators of the application of concepts in contextual situations are the most mastered aspects, while the ability to restate concepts and distinguish examples and non-examples is still weak. These findings emphasize the need to strengthen conceptual understanding through learning strategies that emphasize the representation of meaning and the relationship between concepts so that the development of students’ mathematical competence is more even.